Low Switching Loss Built-In Diode of High-Voltage RC-IGBT with Shortened P+ Emitter - Wei Wu; Yansong Li; Mingkang Yu; Chongbing Gao; Yulu Shu; Yong Chen (Micromachines, 2023)
In this paper, a low switching loss built-in diode of a high-voltage reverse-conducting insulated gate bipolar transistor (RC-IGBT) is proposed without deteriorating IGBT characteristics. It features a particular shortened P+ emitter (SE) in the diode part of RC-IGBT. Firstly, the shortened P+ emitter in the diode part can suppress the hole injection efficiency resulting in the reduced carriers extracted during the reverse recovery process. The peak of the reverse recovery current and switching loss of the built-in diode during reverse recovery is therefore lowered. Simulation results indicate that the diode’s reverse recovery loss of the proposed RC-IGBT is lowered by 20% compared with that of the conventional RC-IGBT. Secondly, the separate design of the P+ emitter prevents the performance of IGBT from deteriorating. Finally, the wafer process of the proposed RC-IGBT is almost the same as that of conventional RC-IGBT, which makes it a promising candidate for manufacturing.